Edugame Interaktif untuk Pembelajaran Literasi Data dan Keuangan Syariah di Sekolah Dasar Islam Terpadu - andi seppewali; Reski Wahyu Yanti; Supardi Muh Said; Ahmad Adivar; Rosmila; Bintang Guntur (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2024)
With the increasing complexity of information and the growing importance of understanding data and sharia financial literacy in society, developing effective and engaging learning methods has become crucial, especially at the elementary school level. The objective of this study is to develop and implement an interactive edugame based on the Guided Discovery approach as a learning tool to enhance students' data and sharia financial literacy. The research method employed is the R&D approach, following the 4D stages: define, design, develop, and disseminate. A comprehensive literature review was conducted to design an interactive edugame that aligns with learning needs and principles. The edugame development process includes graphic design, software coding using HTML5 and Android Studio, as well as iterative testing and revisions. The edugame implementation was carried out at an Integrated Islamic Elementary School, involving training for teachers and students, along with mentoring during the learning process. Furthermore, this study is expected to contribute to the development of innovative learning approaches, particularly in the context of data and sharia financial literacy at the Integrated Islamic Elementary School level.